D’exil et d’américanitude : un entretien avec Linda Bouchard - Bertrand, Simon (Circuit : musiques contemporaines, 2017)
Quebec composer Linda Bouchard (born 1957) is an extremely prolific composer, particularly active on the new music scene in the u.s. where she has lived for lengthy periods since 1989. She has composed a rich and diverse catalogue of works, ranging from orchestral music to more intimist instrumentations, and also using multimedia or improvisation. In this interview, the composer reflects on the question of exile and identity in light of her own experience, thus reliving her own artistic path while also addressing some still burning questions about the place of music creators in the global culture.
Keywords: composer; compositrice; exil; exile; identity; identité; parcours; society; société; trajectory

Björk Digital : escale à Montréal - Marcotte, Nicolas-Alexandre (Circuit : musiques contemporaines, 2017)
An article from Circuit, on Érudit.